Learn more about

Refine search

Results (displaying matches 1-50 of 125) Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
294.a.294.1 294.a \(y^2 + (x^3 + 1)y = x^4 + x^2\) $G_{3,3}$ 0
294.a.8232.1 294.a \(y^2 + (x^3 + 1)y = -2x^4 + 4x^2 - 9x - 14\) $G_{3,3}$ 0
448.a.448.2 448.a \(y^2 + (x^3 + x)y = -2x^4 + 7\) $N(G_{1,3})$ 0
578.a.2312.1 578.a \(y^2 + (x^2 + x)y = x^5 - 2x^4 + 2x^3 - 2x^2 + x\) $G_{3,3}$ 0
600.a.96000.1 600.a \(y^2 + (x + 1)y = 4x^5 + 5x^4 + 3x^3 + 2x^2\) $G_{3,3}$ 0
640.a.81920.1 640.a \(y^2 + x^3y = 3x^4 + 13x^2 + 20\) $N(G_{1,3})$ 0
640.a.81920.2 640.a \(y^2 + x^3y = -3x^4 + 13x^2 - 20\) $N(G_{1,3})$ 0
704.a.45056.1 704.a \(y^2 + y = 4x^5 + 4x^4 - x^3 - 2x^2\) $\mathrm{USp}(4)$ 0
762.a.3048.1 762.a \(y^2 + (x^3 + x^2 + x)y = x^2 + x + 1\) $\mathrm{USp}(4)$ 0
768.a.1536.1 768.a \(y^2 + y = 2x^5 - x^4 - 3x^3 + x\) $\mathrm{USp}(4)$ 0
768.a.4608.1 768.a \(y^2 + (x^3 + x^2 + x + 1)y = -x^3 - x^2 - x - 1\) $\mathrm{USp}(4)$ 0
784.a.1568.1 784.a \(y^2 + (x^3 + x)y = -2x^4 + 3x^2 - 2\) $G_{3,3}$ 0
784.a.43904.1 784.a \(y^2 + (x^3 + x)y = 4x^4 + 27x^2 + 56\) $G_{3,3}$ 0
784.b.12544.1 784.b \(y^2 + (x^3 + x)y = -1\) $G_{3,3}$ 0
784.c.614656.1 784.c \(y^2 = x^5 - 4x^4 - 13x^3 - 9x^2 - x\) $E_3$ 0
800.a.1600.1 800.a \(y^2 + (x^3 + x^2 + x + 1)y = -x^4 - x^2\) $G_{3,3}$ 0
816.a.13872.1 816.a \(y^2 + (x^3 + x^2)y = -2x^4 + 6x^2 - 8x + 3\) $\mathrm{USp}(4)$ 0
826.a.11564.1 826.a \(y^2 + (x^2 + x)y = x^5 + x^4 + 3x^3 - 4x^2 - 4x + 3\) $\mathrm{USp}(4)$ 0
856.a.1712.1 856.a \(y^2 + (x^3 + x)y = -x^4 - x^3 + x\) $\mathrm{USp}(4)$ 0
864.a.1728.1 864.a \(y^2 + (x^3 + x^2 + x + 1)y = x^4 + x^2\) $N(G_{1,3})$ 0
864.a.221184.1 864.a \(y^2 + x^3y = x^5 - 4x^4 - 6x^3 + 33x^2 - 36x + 12\) $N(G_{1,3})$ 0
864.a.442368.1 864.a \(y^2 = x^6 - 4x^4 + 6x^2 - 3\) $N(G_{1,3})$ 0
975.a.63375.1 975.a \(y^2 + (x^3 + 1)y = -x^5 + x^3 + 2x^2 + x - 1\) $\mathrm{USp}(4)$ 0
980.a.7840.1 980.a \(y^2 + (x^2 + x + 1)y = -x^6 + 3x^5 - 3x^4 - x\) $G_{3,3}$ 0
980.a.878080.1 980.a \(y^2 + (x^3 + 1)y = -x^6 + x^5 - 4x^4 + 2x^3 - 4x^2 + x - 1\) $G_{3,3}$ 0
1088.b.2176.2 1088.b \(y^2 + (x^3 + x)y = -5x^4 + 24x^2 - 34\) $N(G_{1,3})$ 0
1122.b.2244.1 1122.b \(y^2 + (x^2 + x)y = x^5 + 7x^4 + 5x^3 - x^2 - x\) $\mathrm{USp}(4)$ 0
1142.b.9136.1 1142.b \(y^2 + (x + 1)y = -x^5 + 3x^4 - 6x^2 + x + 3\) $\mathrm{USp}(4)$ 0
1170.a.10530.1 1170.a \(y^2 + (x^2 + x)y = 15x^6 + 28x^5 + 62x^4 + 59x^3 + 62x^2 + 28x + 15\) $G_{3,3}$ 0
1176.b.16464.1 1176.b \(y^2 + (x + 1)y = -2x^5 + x^2\) $G_{3,3}$ 0
1272.a.122112.1 1272.a \(y^2 + (x^2 + 1)y = 3x^5 + 4x^4 + 2x^3 - x^2 - x\) $\mathrm{USp}(4)$ 0
1280.a.12800.1 1280.a \(y^2 + y = 2x^5 + x^4 - x^3 - x^2\) $\mathrm{USp}(4)$ 0
1296.a.20736.1 1296.a \(y^2 = x^5 - x^4 - 3x^3 + 4x^2 - x\) $E_3$ 0
1312.b.10496.1 1312.b \(y^2 + (x + 1)y = x^6 + x^4 + x^3 + x^2\) $\mathrm{USp}(4)$ 0
1312.b.83968.1 1312.b \(y^2 + xy = 8x^5 - 21x^4 + 15x^3 - x^2 - x\) $\mathrm{USp}(4)$ 0
1338.b.72252.1 1338.b \(y^2 + (x^2 + x)y = x^5 + 7x^4 + 4x^3 - 12x^2 - 6x + 5\) $\mathrm{USp}(4)$ 0
1350.a.5400.1 1350.a \(y^2 + (x^2 + x)y = x^5 + 4x^4 + 4x^3 - x^2 + 3\) $G_{3,3}$ 0
1350.b.6750.1 1350.b \(y^2 + (x^3 + x^2 + x)y = -2x^3 - 2x^2 + 3x - 1\) $G_{3,3}$ 0
1350.c.656100.1 1350.c \(y^2 + (x^2 + x)y = x^5 + x^4 + 4x^3 + x^2 + x\) $G_{3,3}$ 0
1377.a.37179.1 1377.a \(y^2 + (x^2 + x + 1)y = -x^5 + 5x^4 + x^3 - 5x^2 + x + 2\) $\mathrm{USp}(4)$ 0
1416.a.8496.1 1416.a \(y^2 + (x^3 + x)y = x^5 - x^3 - 1\) $\mathrm{USp}(4)$ 0
1440.a.116640.1 1440.a \(y^2 + (x^3 + x)y = 5x^4 + 39x^2 + 90\) $G_{3,3}$ 0
1488.a.71424.1 1488.a \(y^2 = x^5 - x^3 - x^2 - x\) $\mathrm{USp}(4)$ 0
1536.a.12288.1 1536.a \(y^2 = x^5 - 3x^4 + 5x^3 - 4x^2 + 2x\) $\mathrm{USp}(4)$ 0
1600.b.409600.1 1600.b \(y^2 = x^6 - 4x^4 + 4x^2 - 1\) $J(E_1)$ 0
1632.a.52224.1 1632.a \(y^2 + (x^3 + x)y = -x^6 + 11x^4 - 27x^2 + 17\) $G_{3,3}$ 0
1650.a.371250.1 1650.a \(y^2 + (x^2 + x)y = x^5 - 11x^4 + 30x^3 - 11x^2 + x\) $G_{3,3}$ 0
1680.c.241920.1 1680.c \(y^2 + (x^2 + 1)y = 135x^6 - 96x^4 + 22x^2 - 2\) $G_{3,3}$ 0
1740.a.104400.1 1740.a \(y^2 + (x^2 + x)y = 2x^5 - 14x^3 - 5x^2 + 30x\) $\mathrm{USp}(4)$ 0
1746.a.10476.1 1746.a \(y^2 + (x^2 + x + 1)y = x^6 + x^5 + 2x^4 - x\) $\mathrm{USp}(4)$ 0
Next

Download all search results for